Recent advances in nanotechnology for the treatment of metabolic syndrome. Issue 2 (March 2019) - Bahadori, Effat; Farjami, Zahra; Rezayi, Majid; Lngari, Hadis; Darroudi, Majid; Avan, Amir; Ghayour-Mobarhan, Majid
Abstract: Metabolic syndrome is a main clinical challenge of global health which is growing universally. It would be resulted from over-consumption of energy, increased obesity, and lack of movement during life. The metabolic syndrome causes a five-fold increase in the risk of type 2 diabetes mellitus and a double increase in the risk of rising cardiovascular disease over the next 5–10 years. Based on this, more attention has been drawn to the diagnosis and treatment options of this disease. Nanotechnology is one of the preferred methods for improving this disease. This way is a natural development in many health domains, including synthetic and nanostructures. The use of nanoparticles with the purpose of increase the effectiveness of treatment, decrease the side effects and the amount of drug usage, through their small size, permeability and maintenance strength lead to their absorption by target organs. Meanwhile, different nanoparticles with consumption values and particle size have been investigated.